The Influence of Credit Relationship Managers’ Lifestyle and Fraud Potential on Non-Performing Loans in the Banking Sector - Hotman DS; M. Irsan Nasution (Prosiding Seminar Nasional Ilmu Ekonomi dan Akuntansi, 2025)
This study aims to analyze the influence of the lifestyle of credit relationship managers (RMs) and the potential for fraud on the occurrence of non-performing loans in the banking sector. Relationship managers are the spearheads of credit distribution, interacting directly with customers, so their behavior, lifestyle, and integrity have a significant impact on the quality of a bank's credit portfolio. This study uses a qualitative descriptive method with a systematic literature review approach, reviewing various recent studies related to bank employee lifestyles, factors driving fraud, and their correlation with non-performing loans. The results indicate that a consumptive lifestyle disproportionate to income can increase the risk of fraudulent behavior, such as manipulation of credit analysis or collusion with customers, which ultimately results in an increase in non-performing loans. Furthermore, weak internal control systems, pressure to achieve credit targets, and moral hazard exacerbate this risk. A lifestyle that prioritizes social symbols and self-image can also encourage employees to engage in deviant behavior to maintain this lifestyle. Several studies have shown that RMs trapped in a hedonistic lifestyle are more vulnerable to conflicts of interest and violations of professional ethics. Meanwhile, the potential for fraud in banking practices is also influenced by employees' weak personal financial literacy, as well as limited training in risk management and ongoing work ethics. In an organizational context, a work culture oriented toward achieving targets without regard for the quality of credit analysis has the potential to create a work climate that is permissive of irregularities. This study recommends strengthening a culture of integrity through the establishment of a firm code of ethics, technology-based supervision (such as an AI-based fraud detection system), and regular training on a healthy financial lifestyle and risk management for RMs.